Chemical profiling and cytotoxic potential of the n-butanol fraction of Tamarix nilotica flowers - Marwa A. A. Fayed; Riham O. Bakr; Nermeen Yosri; Shaden A. M. Khalifa; Hesham R. El-Seedi; Dalia I. Hamdan; Mohamed S. Refaey (BMC, 2023)
Abstract Background Cancer represents one of the biggest healthcare issues confronting humans and one of the big challenges for scientists in trials to dig into our nature for new remedies or to develop old ones with fewer side effects. Halophytes are widely distributed worldwide in areas of harsh conditions in dunes, and inland deserts, where, to cope with those conditions they synthesize important secondary metabolites highly valued in the medical field. Several Tamarix species are halophytic including T.nilotica which is native to Egypt, with a long history in its tradition, found in its papyri and in folk medicine to treat various ailments. Methods LC-LTQ-MS-MS analysis and 1H-NMR were used to identify the main phytoconstituents in the n- butanol fraction of T.nilotica flowers. The extract was tested  in vitro for its cytotoxic effect against breast (MCF-7) and liver cell carcinoma (Huh-7) using SRB assay. Results T.nilotica n-butanol fraction of the flowers was found to be rich in phenolic content, where, LC-LTQ-MS-MS allowed the tentative identification of thirty-nine metabolites, based on the exact mass, the observed spectra fragmentation patterns, and the literature data, varying between tannins, phenolic acids, and flavonoids. 1H-NMR confirmed the classes tentatively identified. The in-vitro evaluation of the n-butanol fraction showed lower activity on MCF-7 cell lines with IC50 > 100 µg/mL, while the higher promising effect was against Huh-7 cell lines with an IC50= 37 µg/mL. Conclusion Our study suggested that T.nilotica flowers' n-butanol fraction is representing a promising cytotoxic candidate against liver cell carcinoma having potential phytoconstituents with variable targets and signaling pathways.